Studi Eksperimental Viskositas pada Campuran Coolant-Air dengan Beragam Konsentrasi - Takasumiang, Filia Solagratia; Akmal, Faiq; Mahfani, Affan; Umar Umha, Mochamad Aly; Sijabat, Kevin Samuel; Luqyana, Dhiya; Muslimin, Muslimin; Muhamad, Azam Milah (Manutech : Jurnal Teknologi Manufaktur, 2025)
Cooling systems play a crucial role in maintaining the operating temperature of machines, with coolant as a key element to absorb, transfer, and release heat. This study aims to analyze the effect of coolant-water mixture concentration on its dynamic viscosity. Experiments were conducted using three different water concentrations (90%, 80%, and 60%) at a total volume of 250 mL. Data were obtained from flow time measurements through a tube of specific length and diameter, and dynamic viscosity was calculated using Poiseuille's Equation. The results indicate that higher water concentrations reduce dynamic viscosity, making the fluid flow more easily. These findings provide valuable insights for developing more efficient coolant formulations, enhancing the performance of cooling systems in various mechanical applications.